"I had the best of both worlds": transnational sense of belonging-Second-generation Korean Americans' heritage language learning journey. (30th September 2020) - Jeon, Ahrum
Abstract: This study explores how a transnational sense of belonging is constructed within and through heritage language (HL) learning among second-generation Korean American adults throughout their life trajectories. Drawing from eight semi-structured interviews, I show how engaging in HL learning has situated these individuals within transnational social fields, where they, as children of immigrants, were consistently invited through the learning and use of HL to revisit an imagined Koreanness. From being forced speakers of an HL to being willing and inclined to speak it, my participants started to pursue a transnational sense of belonging as a response to the impossibility of being a full American. Their response to transnationalism took place in a less preferable space in which to live, a space where a transnational way of being and living became an alternative or the second-best. Findings from this study suggest that their HL learning trajectories, characterized by care and support from the wider immigrant communities, enabled them to become attuned to the broader transnational community while rearticulating belonging from both worlds.